Role of Matrix Metalloproteinases in Angiogenesis and Its Implications in Asthma - Khuloud Bajbouj; Rakhee K. Ramakrishnan; Qutayba Hamid (Journal of Immunology Research)
Asthma is a chronic airway disorder associated with aberrant inflammatory and remodeling responses. Angiogenesis and associated vascular remodeling are one of the pathological hallmarks of asthma. The mechanisms underlying angiogenesis in asthmatic airways and its clinical relevance represent a relatively nascent field in asthma when compared to other airway remodeling features. Matrix metalloproteinases (MMPs) are proteases that play an important role in both physiological and pathological conditions. In addition to facilitating extracellular matrix turnover, these proteolytic enzymes cleave bioactive molecules, thereby regulating cell signaling. MMPs have been implicated in the pathogenesis of asthma by interacting with both the airway inflammatory cells and the resident structural cells. MMPs also cover a broad range of angiogenic functions, from the degradation of the vascular basement membrane and extracellular matrix remodeling to the release of a variety of angiogenic mediators and growth factors. This review focuses on the contribution of MMPs and the regulatory role exerted by them in angiogenesis and vascular remodeling in asthma as well as addresses their potential as therapeutic targets in ameliorating angiogenesis in asthma.